(untitled) (Nonconventional Technologies Review, 2016)
Since there is no clear definition of the terms "neural network" and "neuronal network", this paper is aimed primarily to establish the difference between them by a rangeof comparative research.As a result, the paper presents some argumentation regarding the differentiation and the point of views of its author, on the use of neural networks in studies and research regarding organizational management.